Knowledge, attitude, and practice (KAP) survey regarding COVID-19 and factors associated with intention to receive a vaccine in kidney transplant recipients: A cross-sectional study: 10.55131/jphd/2024/220310 - Takayama, Tomohiro; Unagami, Kohei; Omoto, Kazuya; Miyata, Satoshi; Takahashi, Kenzo (Journal of Public Health and Development, 2024)
Post-kidney transplant recipients were recommended to take appropriate infection control measures and receive the third or additional doses of COVID-19 vaccines to reduce the risk of severe COVID-19. However, it remained unclear whether prevention of infection was being adequately implemented and what factors were related to vaccination intention. A cross-sectional questionnaire survey was conducted in March 2022 at Yochomachi Clinic in Tokyo, Japan. The purpose of this study was to identify factors associated with vaccine intentions based on the Knowledge, Attitude, and Practice (KAP) survey regarding COVID-19 and how to promote vaccine acceptance to reduce mortality not only during the COVID-19 pandemic but also in future emerging infectious disease pandemics. Of the 497 participants, 435 intended to receive the third dose of COVID-19 vaccines (including those who actually got it), and 62 did not have such intention. Multivariate logistic regression analysis revealed that male sex (OR: 2.856, 95% CI: 1.377-5.921), positive attitude toward COVID-19 (OR: 1.950, 95% CI: 1.399-2.718), and television as a source of information (OR: 4.165, 95% CI: 1.964-8.831) were associated with vaccination intention, whereas patients who trusted family and friends (OR: 0.343, 95% CI: 0.121-0.968) and those who trusted no-one (OR: 0.173, 95% CI: 0.049-0.613) had no vaccination intention. When considering vaccination policies, media outreach to patients should be given high priority, especially for people at higher risk of developing severe symptoms. This approach can promote vaccine acceptance to reduce mortality not only during the COVID-19 pandemic but also in future emerging infectious disease pandemics.